Enhancing EFL Learners' Listening Skills Through Repetition Techniques Using Short Stories The Case of First-Year Middle School Students in Algeria - Hadjadj, Abdelkader; Korichi,Souhila (University of Ammar Theledji -Laghouat, 2020)
The present study investigated the use of the Audio-Lingual Method (ALM), as a teaching method for EFL learners at middle school and the reaction of both teachers and students towards it. First year middle school students have English as a foreign language, academically, for the first time in their education career; they are, then, vocabulary enrichment seekers. The teachers' unawareness of the students' need for a start-up package of basic vocabulary for progression towards mastering EFL is inevitable. This study investigated ALM application and use on first-year middle school. The focus was placed on enhancing the student's listening skills and vocabulary achievement in the view of teachers. The study explores the repetition technique, using the audible short stories. Therefore, it can be hypothesized that if ALM was used appropriately to teach English to first-year middle school students through repetition techniques, using short stories, this would enhance learners’ listening skills, and boost vocabulary storage. To prove this hypothesis, two questionnaires were designed and administered to a group of first year middle school students and teachers across Algeria respectively, to collect data about their attitudes concerning ALM as a teaching method for the teachers and the repetition techniques for the students, with the use of short stories. Results showed that the sample students have the ability to learn vocabulary and sentence patterns easily, while the teachers are the guides who follow the process of students' learning during every class, which gives an advantage to learners to acquire more expressions because of the teachers' academic instructions